Using problem-based learning to promote students critical thinking and mathematical problem-solving skills - Zetriuslita, Zetriuslita; Ariawan, Rezi; Suripah, Suripah; Riyan Hidayat, Riyan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Lampung, 2023)
Objectives: This study aims to promote students ability to think critically and solve mathematical problems in terms of the level of mathematical curiosity using Problem-Based Learning model. Methods: The method of research is quasi-experimental with the mixed method with a sequential explanatory strategy. Findings: There were differences in the students critical thinking and mathematical problem solving skills taught by problem-based learning and conventional learning, but no difference based on the level of mathematical curiosity. Conclusion: Problem-based learning is recommended as an alternative solution for learning in the classroom in an effort to improve critical thinking skills and solve mathematical problems.